Deleted in malignant brain tumors 1 (DMBT1) elicits increased VEGF and decreased IL-6 production in type II lung epithelial cells - Müller, Hanna; Nagel, Christian; Weiß, Christel; Pöschl, Johannes (BMC pulmonary medicine, 2015)
Background: Deleted in malignant brain tumors 1 (DMBT1) is an innate defence protein expressed in the lungs of preterm infants and adults. Recent studies showed that DMBT1 is important in angiogenesis and can bind to different growth factors including VEGF. We aimed at examining relationships between VEGF and IL-6 levels to DMBT1 expression in the lungs of preterm and term infants and in lung epithelial cells in vitro. Methods: We examined by ELISA VEGF levels in 120 tracheal aspirates of 57 preterm and term infants and tested for correlation with different perinatal factors as well as with DMBT1 levels. To examine the effect of DMBT1 on VEGF and IL-6 expression we compared type II lung epithelial A549 cells stably transfected with a DMBT1 expression plasmid (DMBT1+ cells) to A549 cells stably transfected with an empty expression plasmid (DMBT1- cells). The concentrations of VEGF and IL-6 were determined via ELISA in the supernatant of the unstimulated cells and after stimulation with LPS, TNFα and Phorbol-12-myristate-13-acetate (PMA). Results: The VEGF levels in the tracheal aspirates of preterm and term infants were significantly correlated with DMBT1 levels (p = 0.0032), the postnatal age (p = 0.0073) and the presence of neonatal infection/sepsis (p = 0.0002). Unstimulated DMBT1+ A549 cells showed significantly higher VEGF expression (p = 0.0017) than DMBT1- cells. Significantly elevated VEGF levels were also confirmed for DMBT1+ cells after stimulation with TNFα (p = 0.0008), LPS (p = 0.0232) and PMA (p = 0.0025). The IL-6 levels were comparable in DMBT1+ versus DMBT1- cells without stimulation (p = 0.6028), but they were significantly reduced in DMBT1+ cells after stimulation with TNFα (p = 0.0003), LPS (p = 0.0088) and PMA (p = 0.0039). Conclusions: The data indicate that DMBT1 promotes VEGF and suppresses IL-6 production in alveolar tissues, which could point to DMBT1 having a possible role in the transition from inflammation to regeneration and being a potentially useful clinical marker.